SPATIAL IMAGINATION AMONG STUDENTS OF ENGINEERING - NOCAR, David; NOVOTNÝ, Jan; ZDRÁHAL, Tomáš (Trends in education, 2017)
The negative phenomenon of today's educational society is the low level of geometric spatial imagination. For students in technical disciplines it doesn't have to mean more problems during the study but it can also be a limiting factor in their possible creative work in future employment. To address this situation, it is necessary to conduct a thorough analysis of the level of imagination and propose the methods how to increase this level. If we come out of the latest research of education experts for pre-school education and the youngest pupils which point to reality that the influence of ICT technology on manual skills of children is rapidly decreasing, it offers the idea that even in the case of the geometric imagination of the analyzed group may be affected by the fact that by the influence of ICT technologies students meet increasingly only with 3D animations of space objects instead of conventional physical models. Based on an analysis of the level of geometric imagination there were developed methods to develop imagination based on examining groups of eccentric movements of different objects - special subgroups of symmetric groups. The key element here is the composition of these movements which are interpreted in a suitable digital environment which enables these movements to realize. There were built groups of eccentric movements of selected objects in MS Excel. There was implemented a pilot e-learning course called Developing the geometric imagination of students in technical disciplines. Testing and subsequent evaluation of tests results examining the geometric imagination of students in technical disciplines were performed. The test results did not show that exploring the group of eccentric movements of different objects significantly influences the level of geometric imagination of student in technical disciplines. This result was to some extent expected. In further research, the authors will focus on working with physical, not virtual, 3D models.
Keywords: geometric imagination; spatial imagination; 3D model; 3D animation